2021
DOI: 10.3389/fpls.2021.642631
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variability Among Saffron Crocus (Crocus sativus L.) Accessions Characterized by Different Phenotypes

Abstract: This work represents the first epigenomic study carried out on saffron crocus. Five accessions of saffron, showing differences in tepal pigmentation, yield of saffron and flowering time, were analyzed at the epigenetic level by applying a methylation-sensitive restriction enzyme-sequencing (MRE-seq) approach. Five accession-specific hypomethylomes plus a reference hypomethylome, generated by combining the sequence data from the single accessions, were obtained. Assembled sequences were annotated against existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This could be especially useful in species that are propagated clonally, and/or in which the phylogenetic relationships are difficult to infer with classical neutral genetic markers. For instance, a clonally propagated sterile crop such as saffron ( Crocus sativus ), in which the origin and relationships between close species have recently been discovered (Nemati et al, 2019; Schmidt et al, 2019), could benefit from the use of this molecular clock, as differences between accessions could be best explained by DNA methylation (Busconi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This could be especially useful in species that are propagated clonally, and/or in which the phylogenetic relationships are difficult to infer with classical neutral genetic markers. For instance, a clonally propagated sterile crop such as saffron ( Crocus sativus ), in which the origin and relationships between close species have recently been discovered (Nemati et al, 2019; Schmidt et al, 2019), could benefit from the use of this molecular clock, as differences between accessions could be best explained by DNA methylation (Busconi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…AFLP analysis using methylation-sensitive restriction enzyme-sequencing (MRE-seq) gave more insight into saffron’s epigenome [ 52 ]. The study compared the epigenetic profile of 5 phenotypically different, but genetically similar accessions from WSCC germplasm.…”
Section: Diversity Of Saffron and Its Characterizationmentioning
confidence: 99%
“…A heatmap of the 50 highest polymorphic GOs shared between accessions highlighted the presence of two distinct clusters of Indian and Spanish accessions. Twelve GOs showed lower polymorphism in the Spanish accessions than Indian accessions [ 52 ].…”
Section: Diversity Of Saffron and Its Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is generally accepted that triploid saffron crocus emerged only once and was then distributed across the world (Rubio-Moraga et al, 2009;Fluch et al, 2010;Siracusa et al, 2013;Babaei et al, 2014;Alsayied et al, 2015;Nemati et al, 2019). However, a recent study by Busconi et al (2021) reported a surprising amount of genetic differences (singlenucleotide polymorphisms, SNPs). This was detected by a genomewide approach, in which primarily the global DNA methylation across five different saffron accessions was analyzed and a high epigenetic variability has been shown.…”
Section: Absence Of Genetic Variation Among Saffron Accessions Sugges...mentioning
confidence: 99%